Factors associated with prehospital delay in acute stroke: systematic review - Peixoto, Kaliny Oliveira; Correa, Carlos Eduardo Rocha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2017)
Purpose: Stroke is a major cause of death and disability worldwide. Although thrombolytic therapy is effective, it is still underutilized mainly due to delays in patient assistance. A systematic literature review was made to identify the main factors associated with prehospital delay. Methods: A MEDLINE-Pubmed database search in February 2016 retrieved 896 articles, of which 6 were selected for analysis. Results: Low educational level was identified as the most important factor of delay. Means of transportation, transfer between hospitals, as well as onset of symptoms at home were also relevant. Conclusion: We conclude that educational policies and facilitated access to hospital care are keys to minimize barriers to early stroke treatment.